Pengaruh Free Inquiry Approach Berbasis Blended Learning terhadap Keterampilan Komunikasi Mahasiswa - Ernawati; Tri Maniarta Sari (BIOEDUSCIENCE, 2021)
Background: Communication skills are one of the 21st-century learning skills that need to be mastered by students of the Biology Education Study Program of the University of nineteen November Kolaka as prospective teachers to face increasingly complex challenges. The research aims to analyze students' communication skills by applying a free inquiry approach based on blended learning. Method: Quasi Research Experiment with Non-equivalent Control Group Design design. Control groups, lectures by applying conventional models (online group discussions) while experimental groups apply free inquiry approach based on blended learning. Student communication skills data is obtained through observation sheets and analyzed using inferential statistical analysis (t-test) with the help of IBM SPSS Statistic 20 with the formula Analyze-Compare Means-Independent T-Test and descriptive statistics by calculating the average score of each indicator of student communication skills. Results: Obtained a level of significance (p < 0.05) or (4,335 > 2,056) then Ha was accepted and H0 was rejected, meaning there was an effect on the application of free inquiry approach based on blended learning to student communication skills, and the results of the description analysis showed an average score of student communication skills in the experimental class of 74.24 with good categories and in control classes of 60.39 with sufficient categories. Conclusion: Learning by applying a free inquiry approach based on blended learning positively influences students' communication skills.